Research on Saliva Secretion and Composition - Lamy, Elsa (2019)
In the last two decades, saliva gained enormous attention and has become focus of a high number of studies, which resulted in a considerable progress in the knowledge about this biofluid. The technological and analytical advances, including the application of omics approaches, allowed the identification of numerous molecules in saliva, many of which are present in this fluid in proportion to blood. This permitted saliva to be seen as a fluid with potential for diagnosis of different pathologies and physiological conditions. Moreover, the noninvasive nature of its collection is an advantage over serum and reinforced the interest in saliva research. This special issue put together high-quality research, highlighting the diversity of areas in which the study of saliva is of interest.